The Conception of Relationship between Cognition and Faith in Thomas Aquinas’ Philosophy - Stančienė, Dalia Marija (Problemos, 1983)
The article is devoted to an analysis of the conception on the relationship between cognition and faith as presented by Thomas Aquinas (1225-1274), a scholastic. To this aim the sources of Thomist scholasticism are traced back to show how Thomas Aquinas transforms Aristotle’s philosophical views attempting to adapt them to the Christian dogmas. The principal theses by Thomas Aquinas on the essence of being and cognition are revealed and an attempt to estimate Thomas Aquinas’ influence on the development of West-European philosophy is made.